2011
DOI: 10.1111/j.1365-2702.2010.03568.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the temporal artery thermometer a reliable instrument for detecting fever in children?

Abstract: We do not recommend replacement of standard clinical thermometers with temporal artery thermometers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
(55 reference statements)
0
10
0
1
Order By: Relevance
“…The sensitivity of a TM temperature ≥38°C from a recent study of 457 adult ED patients was 74%1 and 58% in 103 hospitalised patients 20. Sensitivities of a cutpoint of 38°C on TA thermometers from three large studies of children were 68%,21 70%22 and 81% 15. Dybwik et al 23 found a TA temperature of 38°C to have a markedly low sensitivity of 53% in 164 adults in an intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of a TM temperature ≥38°C from a recent study of 457 adult ED patients was 74%1 and 58% in 103 hospitalised patients 20. Sensitivities of a cutpoint of 38°C on TA thermometers from three large studies of children were 68%,21 70%22 and 81% 15. Dybwik et al 23 found a TA temperature of 38°C to have a markedly low sensitivity of 53% in 164 adults in an intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of T sk_carotid method for estimating T naso is greater than all previous studies using a standard temperature sensor anywhere on the skin. Temperature measurements on the forehead agree poorly with deep core temperature (12) and are insufficient as a hyper/hypothermia diagnostic tool (30). Skin temperature on the lateral portion of the thigh also correlates poorly with esophageal temperature in young children undergoing elective surgery with general anesthesia (31).…”
Section: Discussionmentioning
confidence: 99%
“…In common clinical practice, noninvasive methods approximate core temperature indirectly. The traditional method of taking oral temperature with a sublingual mercury-in-glass thermometer has, in recent decades, yielded to new technologies that avoid the potential hazards of broken glass and liquid mercury (Zhen et al, 2014;Apa et al, 2013;Batra and Goyal, 2013;El-Radhi and Patel, 2006;Gasim et al, 2013;Jefferies et al, 2011;Penning et al, 2011). The most sensitive temperature sensors are thermistors, which are semiconductors, the electrical resistance of which varies in proportion to temperature (Bhavaraju et al, 2001).…”
Section: Noninvasive Techniquesmentioning
confidence: 99%